Determination of FSI in current urbanization context - Satyarthi, Pushpender (SPA Bhopal, 2018)
This thesis titled “Determination of FSI in current urbanisation context” is done as a part of bachelor of planning programme. The main problems introduced in this thesis at the stage of need of the study for which this whole thesis is done are India is characterized by well-built land use controls and Regulations, the restrictive floor-area ratios or Floor Size Index (FSI) restrictions, is a major problem for a city’s growth. Floor area ratio being the ratio of built area to land area on which it is built. India’s cities are distinguish by tremendously low maximum FSI. FAR gives a clue of how much built up space can be constructed based on different parameters of setbacks, the plot size, etc. but not considering all the major factor of that area which can be land availability. Density, etc. Many literature studies are done related to the topic for better understanding of the concept that how the FSI is distributed in various different region (cities) of India and also compare Indian scenario with other cities of the world. The study is done in Noida because Noida has the highest range of Floor Space Index (FSI) in India, ranging from 2.75 to 3.5 for Green Building its can be consumed up to 3.75. As Noida is way less denser than Delhi or Mumbai, building height restrictions seem to be more favorable to real estate development. This is partly the reason why Noida has become a more prosperous city in the past four decades. At the analysis part the main focus is done on study and find out the relation between FSI and density and FSI and Land use. And study the current development control regulations of Noida and also study the about the availability of extra FSI in the form of premium FSI and TDR. And study what is the current scenario there is there under or over utilization of allotted FSI. And then the proposals are recommended as per the analysis outcome and considering best practices around the world which helped in resolve the identified problem. Suggesting some restriction change in the building regulation is the first most important recommendation (change in Height, Setback, Road width, on the plot size bases,etc). and restrict consumption of extra FSI (premium FSI and TDR) in every part of the Noida by making some zones as per the characteristic and requirement of the area, taking in account of transit oriented development concept, as Delhi master plan 2021 is giving extra FSI to the plots which are falling under TOD influence area developed under some scheme (TD scheme, TP scheme,etc).
Keywords: BPLN (Bachelor of Planning); urbanization